anonymous
  • anonymous
16 = -d + 6
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
kewlgeek555
  • kewlgeek555
I am not sure...I think it would still be 10...
kewlgeek555
  • kewlgeek555
But tha negative sign confuses.
kewlgeek555
  • kewlgeek555
No negative number plus six will get to sixteen.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

petiteme
  • petiteme
transpose 6 to the other side so -6 + 16 = -d Add like terms 10 = -d d=-10 :)
anonymous
  • anonymous
thanks can u help with another ??
kewlgeek555
  • kewlgeek555
I might be able to.
anonymous
  • anonymous
b - 3 over -5 = -15
kewlgeek555
  • kewlgeek555
So is this what you are asking?:\[\frac{ b-3 }{ -5 }=-15\]
anonymous
  • anonymous
yes
kewlgeek555
  • kewlgeek555
Okay, so really this is the same thing as being this:\[(b-3)\div-5=-15\]Now, like I said before - you have to work backwards. Do PEMDAS backwards. SADMEP. So if you do it correctly, it would come out b=78
anonymous
  • anonymous
ok can u explain the steps ?
kewlgeek555
  • kewlgeek555
This is what I did: (-15 * -5) + 3 = b = 78
kewlgeek555
  • kewlgeek555
Or, if you want to me to be more specific: (b - 3) / -5 = -15 (-15 * -5) + 3 = b 75 + 3 = b 78 = b
anonymous
  • anonymous
Thanks ! -10 = 5 + z over -5
kewlgeek555
  • kewlgeek555
\[-10=\frac{ 5+2 }{ 5 }\]\[-10=(5+2)\div5\]\[(-10\times5)-5\]\[-50-5\]\[z=-55\]
anonymous
  • anonymous
13 = -8p - 3 + 9p
kewlgeek555
  • kewlgeek555
I got 16, but based on my special calculator it is 4, so the answer is 4.
anonymous
  • anonymous
Can u explain the steps
kewlgeek555
  • kewlgeek555
I can't because when I tried to do it I actually did it wrong and checked my work with my special calculator and it said I was wrong so...let me see.
anonymous
  • anonymous
ok
kewlgeek555
  • kewlgeek555
Yeah, I can't seem to figure out how I got that one wrong. :-/
anonymous
  • anonymous
I'm thinking I have to multiply -8p and 9p since they are like terms
anonymous
  • anonymous
then it becomes 13 = -7 - 3 and then -72 - 3 which becomes -75 then multiply 13 and -75 giving me -975 hmm that seems way too high
kewlgeek555
  • kewlgeek555
This is what I thought: 13 = -8p - 3 + 9p I combine the like terms, which are -8p and 9p by adding 9 to -8 (because you always keep the sign before the number with the number), making the equation 13 = 1p - 3. From there I go to (13 + 3) / 1 Then 16 / 1 And 16 = p
kewlgeek555
  • kewlgeek555
But based on my calculator I am wrong.
kewlgeek555
  • kewlgeek555
But hey, if you have to show your work then if you put that then you'll be at least get 50% credit for trying to solve.
anonymous
  • anonymous
http://www.geteasysolution.com/13=-9p+13+9p
anonymous
  • anonymous
Simplifying 13 = -9p + 13 + 9p Reorder the terms: 13 = 13 + -9p + 9p Combine like terms: -9p + 9p = 0 13 = 13 + 0 13 = 13 Add '-13' to each side of the equation. 13 + -13 = 13 + -13 Combine like terms: 13 + -13 = 0 0 = 13 + -13 Combine like terms: 13 + -13 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions
anonymous
  • anonymous
that's probably why you're getting two different answers
kewlgeek555
  • kewlgeek555
Wow. I am actually about to leave my computer. Let me try my fastest. Okay, instead of 13 = 13 + 9p + 9p, I would do 13 = 9p + 9p + 13. Anywho, the next step would be combining like terms which would be -9 + 9 = 0p. 13 = 0p + 13. 13 - 13 = 0. 0 / 0 = p = ERROR.
kewlgeek555
  • kewlgeek555
Hm...I don't know. @campbell_st @savannaxx_ @Firejay5 might help. Let me check my special calculator.
anonymous
  • anonymous
yeaa that's why. k thanks for the help
kewlgeek555
  • kewlgeek555
Oh. So you are actually right. P = Always true, or all real numbers.
kewlgeek555
  • kewlgeek555
You are very welcome.
Firejay5
  • Firejay5
Thanks ! -10 = 5 + z over -5, the answer is actually 45 not -55
anonymous
  • anonymous
Actually no. since it's a negative 55 u would do the opposite and add not subtract.
Firejay5
  • Firejay5
no it's wrong \[\frac{ z + 5 }{ -5 } = -10\]
Firejay5
  • Firejay5
you have to multiply -5 to both sides to cancel out the denominator -10 * -5 = 50; then you have z + 5 = 50; substract 5 from both sides and you get z = 45
Firejay5
  • Firejay5
13 = -8p - 3 + 9p = x = 16
anonymous
  • anonymous
actually the -10 is on the other side. whatever u say
Firejay5
  • Firejay5
It's better for me to organize my variables
Firejay5
  • Firejay5
either way you change it's still correct, but it's just switched
Firejay5
  • Firejay5
I did this stuff in Algebra II you have to get the denominator to cancel out by multiplying
Firejay5
  • Firejay5
plug -55 back into the regular equation and you will get 10 not -10

Looking for something else?

Not the answer you are looking for? Search for more explanations.